Computer Assisted Test Construction in the BYU Library School - Wood, Lewis Jay. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Computer assisted test construction (CATC) is a new testing technique that seems to provide ease and flexibility for faculty members and students. The purpose of this paper was to verify that student test scores are not adversely affected by implementation of CATC. Two sections of a basic course in cataloging were tested for one semester. One section of 30 students was used as a control group while the other 20 students served as the experimental group. The students were pre-tested and then received class instruction. During the course of the semester, unit exams were administered. Exams for the control group were prepared by the course instructor. The experimental group's exams were compiled of random questions selected by the computer from the item bank. The analysis of scores from a post-test confirmed the hypothesis there would be no detrimental effect upon test scores for students tested with the CATC system. The pre-test used in the study is included in the appendix. (Author/JAB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Item Banks; Library Education; Pretesting; Pretests Posttests; Test Construction; Testing; Tests; Brigham Young University UT; Reports, Research